Tawhid Values in Tafsir Al-Qur’anul Karim by Shaykh Abdul Halim Hasan and Implications for Contemporary Aqidah Education - Holid, Syahrul; Najari, Muhammad; Nahar, Syamsu; Mukhlisa, Ainna (Fitrah: Journal of Islamic Education, 2025)
The lack of research on the intellectual heritage of Nusantara scholars has resulted in limited academic recognition of local contributions to the development of Islamic creed education. One significant figure who has not been extensively studied is Shaykh Abdul Halim Hasan, particularly his Tafsir Al-Qur’anul Karim, which contains values of tawhid. This study aims to examine the concepts of tauhid rububiyyah, uluhiyyah, and asma’ wa sifat in his tafsir and their implications for contemporary Islamic education. The method used is qualitative with a library research approach, and the analysis is conducted thematically and contextually. The results of the study indicate that Shaykh Abdul Halim’s interpretation emphasizes the strengthening of faith, character building, and the instillation of moral and spiritual values based on tauhid. Each dimension of tauhid explained has direct relevance to contemporary Islamic education strategies. The implications of this study highlight the importance of integrating tauhid values into the curriculum of akidah education, and utilizing the works of local scholars as references in developing contextual, transformative, and value-based learning.